On Two Methods for Analyzing the Activities of Enterprises in the Real Sector of the Economy in the Commodity Market - A. N. Tsatsulin (Управленческое консультирование)
The article is devoted to the consideration of two conceptual approaches to assessing the state and prospects for the development of economic entities in the real sector of the economy on the example of the so-called “golden rule” of the economy and the balanced scorecard. The relevance of the material of the article lies in the fact that the borrowed foreign methodology for studying the actual state of the enterprise, however, allows not only to assess the production and human potential of an economic entity in dynamics of the analyzed period, but also to assist in the development of enterprise development plans for the future of various durations and the development of an individual development strategy in a particular market space in the areas of investment, innovative improvement, marketing policy development, corporate culture, increasing market activity, strengthening business reputation and competitive positions. The purpose of the study is to test the effectiveness of the methodology of both approaches and the effectiveness of the tools used on the examples of enterprises in the real sector of the economy. The index method of statistical research was used as a toolkit when fulfilling both the golden rule and the balanced system of standard technical and economic indicators. The calculations are summarized in tables, illustrated with graphic drawings. The results of the analysis are discussed and commented on taking into account the specific characteristics of the sectoral activities of the selected economic entities. The article draws the necessary conclusions regarding the similarities and differences of the considered methodologies and assesses the prospects for their use in solving applied problems of analysis.